Dating patterns and attitudes of female fifth formers in an inner-city secondary school in Kuala Lumpur - Purushothaman, Nirmala (1997)
Dating, while providing an opportunity for necessary emotional development in adolescents can also lead to disturbing sociological consequences. Rising levels of sexual pro miscuity, teenage pregnancy, abortion and other negative consequences of dating has been widely observed. Based on this scenario, this descriptive case study attempts to identify the general dating patterns and attitudes of female fifth formers (N=206) in an inner-city school in Kuala Lumpur. The following aspects of dating are examined: reasons for dating, dating code, dating preferences, intimacy, effects on selfesteem, consequences of dating and effects of parental restrictions. It was found that widespread dating occurs among adolescents at a young age, and it quickly becomes a central part of their social lives. This is generally consistent among all three major races in Malaysia, and many will date secretly to avoid censure from their parents. Though most dating begins in groups, adolescents express a desire to date exclusively with one partner after only a short period of time. The level of sexual activity, however, does not correspond with the high level of dating. The vast majority still believes that sex should be reserved for marriage, and many refrained from almost all intimate relations. Conservative parents will be relieved to know that Malaysian adolescents are not as liberal as they may seem. One must still remain painfully aware, however, of the minority who are sexually active, and are not necessarily aware of the risks involved. This study revealed that many students are completely unaware of how to practice safe sex or avoid pregnancy.